STUDENTS’ PERCEPTION TOWARD PROBLEMS FACED IN SPEAKING ENGLISH OUTSIDE THE CLASSROOM - Rahil Helmi (English Language Education Department, Faculty of Teacher Training and Education, Syekh-Yusuf Islamic University (PBI FKIP UNIS), 2023)
This research paper investigated the problems faced by the students in speaking English outside the classroom. The population of this research is all of the English Department students of Universitas Islam Negeri (UIN) Ar- Raniry. The samples are the students starting academic year 2021. This research was conducted to study the perception of the students’ problems faced in speaking English outside the classroom. A mixed-methods approach adopted to gather comprehensive data and insights. The primary data collection methods included observation and questionnaire. Two main problems are faced by students: linguistic and non-linguistic issues. There are five elements occur in linguistic problems:(1) Vocabulary, (2) grammar, (3) pronunciation, (4) comprehension, and (5) Fluency. While non-linguistic problems are: (1) self-confidence, (2) embarrassment, (3) lack of partners, (4) and pride. In addition, this research also found the percentage of English being used based on students’ perception in English Department of language teaching. It showed 46 % of the environment, 30 % of the staffs and the lecturers, and 24 % of the students.